2019
DOI: 10.1016/j.apgeochem.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy, solid-phase fractionation and chemical extraction to assess the mobility and availability of arsenic in an urban environment

Abstract: A multidisciplinary approach, using chemical extraction and analytical structural techniques, has been used to assess the mobility and availability of arsenic in urban soil samples from two current housing sites. Arsenic concentrations in each site varied between 126-1,660 mg/kg (Site A) and 40-24,900 mg/kg (Site B). Using a non-specific sequential extraction approach, it was possible to identify two distinct, site specific, As-containing fractions i.e. Fe-As-Ca (Site A) and As-Fe (Site B), in the soils. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…The solid-phase fractionation of the test soils was determined using the Chemometric Identification of Substrates and Elements Distributions (CISED) method [12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-phase fractionation of the test soils was determined using the Chemometric Identification of Substrates and Elements Distributions (CISED) method [12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…80%) and a much lower variability in Ca content suggesting it represents a purer form of Ca carbonate than cluster 4. The peaks of extraction of each component are more variable than those in cluster 4 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). This may suggest that some of these components are more crystalline than those in cluster 4 which may be a more fine-grained amorphous material.…”
Section: Interpretation Of the Geochemical Clustersmentioning
confidence: 99%
“…A total of 14 extracts per dust were obtained for analysis of 30 elements by ICP-MS. Subsequently, the multi-element extract data were subject to a chemometric self-modelling mixture resolution (SMMR) procedure, as described elsewhere [32,34]. For data quality control, blanks, and reference material (BGS102) were included in the extraction procedure.…”
Section: Instrumentationmentioning
confidence: 99%
“…An earlier version of this same reference material has been analysed previously by Cave and co-authors [35]. Several studies were shown the CISED as a useful methodology for understanding the biogeochemistry of trace elements in soil and dust [30,34,36].…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation